Inflation, Interest Rates, and Money Supply as Drivers of Exchange Rate Movements in ASEAN Countries - Dara Maqfirah; Khairita Hasbi (Majalah Bisnis & IPTEK, 2026)
The present study investigates the determinants of exchange rate fluctuations across six ASEAN economies, Indonesia, Malaysia, Myanmar, Singapore, the Philippines, and Thailand, over the 2020–2024 period. Divergent macroeconomic trajectories among member states, particularly with respect to price stability, central bank policy stances, and monetary liquidity conditions, have generated persistent exchange rate instability throughout the region. These pressures were further compounded by the economic fallout of the COVID-19 pandemic, which prompted widespread adoption of expansionary monetary policies across the region, later followed by tightening cycles as central banks moved toward normalization. A purposive sampling approach was applied to select six countries based on two criteria: availability of complete and consistent data throughout the observation window, and representativeness of the region's diverse economic development profiles. Panel data estimation was conducted using the Fixed Effects Model (FEM), selected on the basis of the Chow test and theoretical justification related to structural heterogeneity across countries. Data were obtained from the IMF's International Financial Statistics (IFS) and supplemented by Trading Economics. Empirical results indicate that inflation exerts a positive and significant effect on exchange rates (p = 0.0057), in line with the Purchasing Power Parity (PPP) framework, whereby higher domestic price levels are associated with domestic currency depreciation. Interest rates show a negative but statistically insignificant effect, a pattern attributed to the heterogeneous monetary policy frameworks operating across ASEAN — including Singapore's exchange rate-based mechanism and Myanmar's fixed rate policy — which collectively weaken the aggregate statistical relationship. Money supply growth (M2) exhibits a negative and significant effect, indicating that monetary expansion is associated with exchange rate strengthening in the log-transformed model. The model achieves an exceptionally high explanatory power, with R² = 0.9994 and F-statistic = 5213.750 (p = 0.0000), confirming that virtually all cross-country exchange rate variation is captured by the three regressors alongside country-specific fixed effects. These findings highlight the centrality of inflation control and monetary discipline in preserving exchange rate stability across the ASEAN region.